Konseptualisasi Pendidikan Islam dalam Keluarga - Siti Yumnah (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2020)
Islamic education is essentially the first place for conducting education in which each family interacts with one another to help one another in the good. More than that, personality becomes the main thing to prioritize in upholding religious values that actually existed in children when they were born. The family as the first madrasa needs to be supported by a family environment that firmly plants religious seeds on the basis of building noble morals in all elements of daily life. The role of parents is very urgent to have a significant influence in paying attention to physical and spiritual needs, such as clothing, food and shelter, which form a unified whole in family education.